Research of Technology Solutions and Operation Countermeasures to Telephone Fraud Prevention and Control - Lika Li; Zexiong Ma; Qingnian Chen; Cheng Li (Dianxin kexue)
Currently the incidence of using telephone for fraud is growing up to a new high level, cause huge losses to the people property. According to the root cause analysis, telephone fraud mechanism and behavior characteristics were discussed, network security model and the control system were researched, the recommending of core network number protection ability to ascend was proposed, and a set of early warning and intercept technology system based on big data model of signaling was developed. The real network testing and effect, as well as the key operations management countermeasures were presented.